2020
DOI: 10.1177/2152656720956596
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cut-off Points of Eosinophils, Nasal Polyp, and Lund-Mackay Scores to Predict Surgery in Nasal Polyposis: A Real-World Study

Abstract: Background Developing tools to identify chronic rhinosinusitis with nasal polyps (CRSwNP) patients requiring surgical treatment would help clinicians treat patients more effectively. The aim of this retrospective cross-sectional study was to identify cut-off values ​​for eosinophil percentage, nasal polyps (NP), and Lund-Mackay (LM) scores that may predict the need for surgical treatment in Finnish CRSwNP patients. Methods Data of CRSwNP patients (N = 378) undergoing consultation for ESS in 2001–19 were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
3
3
0
Order By: Relevance
“…Additionally, prior study showed that the cut-off value of blood eosinophil count (>0.26 Â 10 9 /L) might have relatively good, predictive potential in patients with nasal polyps who require surgical treatment. 28 In the present study, we further found that there was no significant difference in the rate of uncontrolled subjects between IH-tissue-eos and H-tissue-eos subgroups, whereas the IHblood-eos patients had higher rates of uncontrolled subjects and asthma and CT scores than the H-blood-eos patients (p = .09, Table 2). These results imply that blood eosinophils might possibly have a larger influence on treatment outcomes and disease severity than tissue eosinophils.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Additionally, prior study showed that the cut-off value of blood eosinophil count (>0.26 Â 10 9 /L) might have relatively good, predictive potential in patients with nasal polyps who require surgical treatment. 28 In the present study, we further found that there was no significant difference in the rate of uncontrolled subjects between IH-tissue-eos and H-tissue-eos subgroups, whereas the IHblood-eos patients had higher rates of uncontrolled subjects and asthma and CT scores than the H-blood-eos patients (p = .09, Table 2). These results imply that blood eosinophils might possibly have a larger influence on treatment outcomes and disease severity than tissue eosinophils.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, our studies revealed that the blood eosinophil count and the tissue eosinophil percentage are independently associated with an increased risk for poor disease control in CRSwNP patients receiving current standard‐of‐care therapy after adjustments for covariates previously shown to relate to poor treatment outcome. Additionally, prior study showed that the cut‐off value of blood eosinophil count (>0.26 × 10 9 /L) might have relatively good, predictive potential in patients with nasal polyps who require surgical treatment 28 . In the present study, we further found that there was no significant difference in the rate of uncontrolled subjects between IH‐tissue‐eos and H‐tissue‐eos subgroups, whereas the IH‐blood‐eos patients had higher rates of uncontrolled subjects and asthma and CT scores than the H‐blood‐eos patients ( p = .09, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed that CRSwNP, asthma, and NERD are important predictors of revision ESS also at the individual level. In accordance to this, previous studies have demonstrated on hospital population level that several factors are associated with the CRS recurrence and/or revision ESS, such as CRSwNP, asthma, AR, NERD, eosinophilia and smoking 1,7,23,24 . CRSwNP patients with co-morbid asthma and/or NERD have an increased risk for recurrence and revision ESS, although these patients seem benefit from initial ESS 13,19,[25][26][27] .…”
Section: Discussionsupporting
confidence: 77%
“…Our study also showed that CRSwNP, asthma and NERD represent important predictors of revision ESS at the individual level. In accordance with this, previous studies demonstrated at the hospital population level that several factors associate with CRS recurrence and/or revision ESS, including CRSwNP, asthma, allergic rhinitis, NERD, eosinophilia and smoking [1,13,57,58]. CRSwNP patients with a comorbidity of asthma and/or NERD carry an increased risk for recurrence and revision ESS, although these patients appear to benefit from an initial ESS [19,41,[59][60][61].…”
Section: Plos Onesupporting
confidence: 70%